Legal Protection against Default by The Debtor in The Implementation of A Lease Agreement (Building, According to Verdict Number: 63/Pdt.G/2018/PN.Skt) - Andika Dwi Sulistyo; Arief Budiono; Gamar Muhdar (Proceeding International Conference Restructuring and Transforming Law, 2024)
This research focuses on legal protection for debtors who bind themselves to an agreement and in the end there is a misuse of rental goods by the debtor. The basis of this research refers to the decision of the Surakarta District Court, and in this problematic the Surakarta District Court is authorized and decides the case. This research uses a normative juridical approach method and uses secondary data. The results of this study indicate that the legal protection given to creditors for acts of default by the debtor has been pursued by the rules of law if the debtor does not fulfill or does not do what has been promised, he has committed an act of default and returned the object of dispute to be returned to the creditor. The judge's consideration is by the applicable laws relating to the default committed by the defendant.